2021
DOI: 10.1016/j.jogc.2021.02.037
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of COVID-19 on pregnant and postpartum individuals: a mixed methods exploration

Abstract: Objectives To explore the psychosocial and behavioural responses of pregnant and postpartum individuals during the COVID-19 pandemic in order to develop strategies for healthcare providers to support patients through a pandemic. Methods Mixed-methods study of patients in an urban Toronto multidisciplinary Family Health Team who were between 20 weeks pregnant and 5 months postpartum from June to August 2020. Using a questionnaire and qualitative interviews, we explored p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The lack of differences found for women with or without other children indicates the importance of uplifting feelings about pregnancy, regardless of whether women are transitioning into motherhood or already have parenting experience. The COVID-19 pandemic introduced new stressors for pregnant women (Kolker et al, 2021;Wall and Dempsey, 2022), but our data suggest that there might also be some pandemic-related benefits, which, to our knowledge, have not been studied previously. In our sample, women who focused more on these pandemic-related uplifts than hassles were more positive, less lonely, and less depressed/anxious.…”
Section: Positivity and Pregnancy Enjoymentmentioning
confidence: 63%
See 4 more Smart Citations
“…The lack of differences found for women with or without other children indicates the importance of uplifting feelings about pregnancy, regardless of whether women are transitioning into motherhood or already have parenting experience. The COVID-19 pandemic introduced new stressors for pregnant women (Kolker et al, 2021;Wall and Dempsey, 2022), but our data suggest that there might also be some pandemic-related benefits, which, to our knowledge, have not been studied previously. In our sample, women who focused more on these pandemic-related uplifts than hassles were more positive, less lonely, and less depressed/anxious.…”
Section: Positivity and Pregnancy Enjoymentmentioning
confidence: 63%
“…Loneliness is also detrimental to women’s and children’s health and is often co-occurring with prenatal depression (Luoma et al, 2019). Nascent survey research has found that pregnant women frequently report feelings of loneliness during social distancing policies (Giurgescu et al, 2022; Kolker et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations